THE EFFECTIVENESS OF MODEL-ELICITING ACTIVITIES AND COOPERATIVE LEARNING MODELS OF PROBLEM SOLVING TYPE ON THE STUDENT’S UNDERSTANDING OF MATHEMATICAL CONCEPT - Apriliani Fitriya Damayanti; Suparman Suparman (Universitas Ahmad Dahlan, 2017)
Lack of understanding of a concept would affect student learning outcomes, especially in mathematics. That matter which led to lower student learning outcomes. This study aims to determine the differences in the ability of understanding mathematical concepts that use model-eliciting Activities and cooperative learning model of problem-solving as well as to compare the effectiveness of the model-eliciting Activities and cooperative learning model of problem-solving on the ability of understanding mathematical concepts at eleven grade of TKJ’s student in SMK Negeri 2 Depok Yogyakarta of even semester at academic year of 2016/2017. The population in this study is a class XI TKJ SMK Negeri 2 Depok Yogyakarta. Selection of the sample by means of a non-probability sampling with purposive technique, the sample selection based on objective and specific considerations. The sample in this research is class XI TKJ A as an experimental class 1 and class XI TKJ B as the experimental class 2. Of each class of samples taken 5 students for a testing-grade. The research design in this study is non-equivalent (pretest-posttest) Control-Group Design. The data collection method is a method of documentation and tests. The instrument was a matter of the description. Test data collection instruments used validity and test data analysis used reliability. The analysis of the data is the prerequisite test analysis including normality test and homogeneity test; and hypothesis testing using t-test. The result of the research on the significance level on 5% and df = 52 indicates that: (1) There is the difference between the ability to understand mathematical concepts in learning that uses the model-eliciting activities with learning that uses the cooperative model of the problem-solving type. It can be seen that greater than . (2) Learning mathematics students who use model-eliciting activities more effective than learning using a cooperative learning model of the problem-solving type. It can be seen that greater than .